IMPLEMENTASI PENDIDIKAN KARAKTER PADA MATA PELAJARAN PAI DI SMA AL-RIFA’IE GONDANGLEGI - Nanda Asmaniyah; Ika Ratih Sulistiani; Ika Anggraheni (Vicratina : Jurnal Ilmiah Keagamaan, 2019)
Education is an aspect that has a strategic role in building intelligence as well as the personality of the human child for the better. Character education is a cultivation of character values to all schools which include elements of knowledge, awareness or willingness and actions to perform character values. Character education must also be based on Islamic religious education for Muslims and must begin at an early age. School is one of the determinants of achieving character education. Therefore, researchers conducted research on the implementation of character education in Islamic Religion subjects at Al-Rifa'ie Gondanglegi High School. This study used qualitative research methods. The results showed that the implementation of character education in the applied character education method was in the form of a Classic character education model.